Implementation of the Islamic Form Concept in the Main Building of the Islamic Center Area in Sidoarjo City - M. Fatchur Rozi; Wiwik Widyo Widjajanti; Ika Ratniarsih (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
Islamic Center in Sidoarjo City is a building area that aims to facilitate the growth and development of Islam in Sidoarjo City. This is due to the absence of facilities that provide for Islamic religious activities. With the existence of this building area, it is expected to be able to accommodate scholars and Muslims to develop and maintain the values of Islam. Through the application of the Islamic Architecture theme, the buildings in this area apply the concept of Islamic Geometry to the form of the building with the aim of creating a form of Islamic architecture that is able to express the characteristics of Islamic architecture. The concept of Islamic geometry in the form of architecture will focus on creating an attractive, charming design that has deep meaning. Islamic Geometry Design can include various elements that make the building an attractive and inviting sight. The concept of this form must create an eye-catching form for people towards the surrounding environment, so that the existing building form is able to respond to the conditions of the surrounding environment.